Produksi Umpan Rayap dari Limbah Bahan Organik dan Efektivitasnya dalam Pengendalian Serangan Coptotermes sp. - Agung Nugrawan Kutana; Musrizal Muin; Astuti Arif (Forestry Faculty of Universitas Hasanuddin, 2018)
Damages of building construction due to termite attacks have caused high economic losses and therefore, efforts are continuously developed to overcome the serious problem. Baiting system is one way to control termite attacks as it consists of acceptable termite food sources, combined with a slow-acting substance lethal to termites. This study was conducted to produce termite bait materials from organic waste mixtures and evaluate its effectiveness against termite attacks in the field. The termite baits were produced by mixing paper, cardboard, and degraded pine wood, combined with leaves of Melaleuca leucadendron Linn assumed to be toxic to termites. Tapioca starch was used as glue and added to the organic materials mixture before pressed at room temperature with the target density of 1.0 g/cm3. The produced baits were placed in the field with signs of heavy attacks of termites, Coptotermes sp., and observed every three days for the termite elimination. Results showed that the bait formulation enables to significantly eliminate the termite attacks with high attractant properties. However, its effectiveness was still lower than the commercial bait due to its high capacity of water absorption, indicating the importance of further research on its mixture and glue formulation.